2003
DOI: 10.1128/aem.69.8.4359-4366.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a Nitrilase Gene from the CyanobacteriumSynechocystissp. Strain PCC6803 and Heterologous Expression and Characterization of the Encoded Protein

Abstract: The gene encoding a putative nitrilase was identified in the genome sequence of the photosynthetic cyanobacterium Synechocystis sp. strain PCC6803. The gene was amplified by PCR and cloned into an expression vector. The encoded protein was heterologously expressed in the native form and as a His-tagged protein in Escherichia coli, and the recombinant strains were shown to convert benzonitrile to benzoate. The active enzyme was purified to homogeneity and shown by gel filtration to consist probably of 10 subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Analysis of the surrounding gene region revealed that this gene appears as the first gene of a cluster which had been previously described in the context of the following gene, sll0784 (26). The sll0784 gene encodes a nitrilase which has already been characterized biochemically (14). The genes in the cluster occur in the following order: (i) a hypothetical protein (sll0783), (ii) a nitrilase (sll0784), (iii) a radical S-adenosylmethionine superfamily member (sll0785), (iv) a potential acetyltransferase (sll0786), (v) an AIR synthase-related protein (sll0787), (vi) a hypothetical protein (ssl1464), and (vii) a flavoprotein predicted to be involved in K ϩ transport (slr0801) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the surrounding gene region revealed that this gene appears as the first gene of a cluster which had been previously described in the context of the following gene, sll0784 (26). The sll0784 gene encodes a nitrilase which has already been characterized biochemically (14). The genes in the cluster occur in the following order: (i) a hypothetical protein (sll0783), (ii) a nitrilase (sll0784), (iii) a radical S-adenosylmethionine superfamily member (sll0785), (iv) a potential acetyltransferase (sll0786), (v) an AIR synthase-related protein (sll0787), (vi) a hypothetical protein (ssl1464), and (vii) a flavoprotein predicted to be involved in K ϩ transport (slr0801) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we found a similar strong decline in transcript abundances for the genes sll0783 to sll0787 (Table III). With exception of Sll0784, the nitrilase MerR (Heinemann et al, 2003), the functions of all other encoded proteins are unknown. By the action of nitrilases, which hydrolyze nitriles to the corresponding carboxylic acids and ammonium, many bacteria like Pseudomonas fluorescens EBC191 can use nitriles as nitrogen source (Kiziak et al, 2005).…”
Section: Further Newly Identified C I Responsive Genes After Long-termentioning
confidence: 99%
“…Escherichia coli JM109 was used as the host strain for all plasmids. The cultivation and induction conditions for the recombinant strains used were described previously (16,20,40). Enzyme assays.…”
Section: Methodsmentioning
confidence: 99%
“…The construction of plasmids pIK7, pIK9, and pDHE22, which encode the nitrilases from Alcaligenes faecalis ATCC 8750, Pseudomonas fluorescens EBC191, and Synechocystis sp. strain PCC6803, respectively, was described previously (16,20,21). The gene for the rhodococcal nitrilase was amplified from a nitrileconverting Rhodococcus rhodochrous strain.…”
Section: Methodsmentioning
confidence: 99%